Fighting famine in Southern Africa: steps out of the crisis [in Japanese] - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
About 10 million people in southern Africa—Lesotho, Malawi, Mozambique, Swaziland, Zambia, and Zimbabwe—are experiencing famine or the threat of famine.The immediate causes of the current crisis are drought, flooding, and low levels of crop planting.What has made these countries so vulnerable to famine, however, is chronic poverty and inadequate policies. Now these conditions have combined to result in severe shortfalls in food production and in turn high prices for maize, the staple food of the region. The key to overcoming this famine is appropriate and effective policies. Described here are the policy approaches that IFPRI research in Africa has shown to be effective in fighting famine.